An equilibrium model of bus and car travel over a road network - 423390 Wigan, M. Ramsay; Bamford, T. J. G.; Transport and Road Research Laboratory (Great Britain) (Crowthorne, Berkshire : Transport and Road Research Laboratory, 1973)
08